Bioactive 2-pyrone metabolites from an endophytic Phomopsis asparagi SWUKJ5.2020 of Kadsura angustifolia. (December 2017) - Song, Hong-Chuan; Qin, Dan; Han, Mei-Jun; Wang, Ling; Zhang, Kuo; Dong, Jin-Yan
Graphical abstract: Highlights: Five new 2-pyrone metabolites was isolated from cultures of the fungus Phomopsis asparagi SWUKJ5.2020. These metabolites have the rare 5- substituted 2-pyrone skeleton in the 2-pyrone class of compounds. The compounds (3–5 ) in this paper exhibited notable cytotoxicity against HL-60 and K562 cells. Abstract: Five new 2-pyrone metabolites, phomaspyrones A–E (1–5 ) along with three known compounds, macommelin-8, 9-diol (6 ), macommelin-9-ol (7 ), and macommelin (8 ), were isolated from the culture broth of an endophytic fungus Phomopsis asparagi SWUKJ5.2020 of medicinal plant Kadsura angustifolia by sequentially purification over silica gel, Sephadex LH-20 column chromatography and preparative HPLC. Their structures were elucidated on the basis of spectroscopic analysis, including two-dimensional (2D) NMR and HRMS (ESI-TOF) data. Among them, compounds3 –5 exhibited notable cytotoxicity against HL-60 and K562 cells with IC50 values of below 10 μg/mL better than those of the other isolated metabolites (IC50 = 10.6–26.6 μg/mL). The results showed that the keto or hemiketal functionality might play an important role in cytotoxic activity of this class of compounds.